2001
DOI: 10.1101/gad.192601
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinase phosphatase is required for genotoxic stress relief inArabidopsis

Abstract: Genotoxic stress activates complex cellular responses allowing for the repair of DNA damage and proper cell recovery. Although plants are exposed constantly to increasing solar UV irradiation, the signaling cascades activated by genotoxic environments are largely unknown. We have identified an Arabidopsis mutant (mkp1) hypersensitive to genotoxic stress treatments (UV-C and methyl methanesulphonate) due to disruption of a gene that encodes an Arabidopsis homolog of mitogen-activated protein kinase phosphatase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
146
2
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(154 citation statements)
references
References 71 publications
2
146
2
2
Order By: Relevance
“…The Arabidopsis genome encodes five candidate MKPs (AtMKP1, At3g06110, DsPTP1, PHS1, and IBR5), based on their catalytic domain sequence conservation (18), and several of these have been implicated in various biological scenarios. Mutants of AtMKP1 were reported to show hypersensitivity to genotoxic stress, but not to other oxidant stresses (20), and to also be less sensitive to elevated salt levels in the growth medium. Subsequent analysis revealed that AtMKP1 interacts with MPK6 and, to a lesser extent, with MPK3 and MPK4 in yeast two-hybrid screens (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Arabidopsis genome encodes five candidate MKPs (AtMKP1, At3g06110, DsPTP1, PHS1, and IBR5), based on their catalytic domain sequence conservation (18), and several of these have been implicated in various biological scenarios. Mutants of AtMKP1 were reported to show hypersensitivity to genotoxic stress, but not to other oxidant stresses (20), and to also be less sensitive to elevated salt levels in the growth medium. Subsequent analysis revealed that AtMKP1 interacts with MPK6 and, to a lesser extent, with MPK3 and MPK4 in yeast two-hybrid screens (21).…”
Section: Discussionmentioning
confidence: 99%
“…However, no physiological context has yet been defined for DsPTP1 activity. AtMKP1, on the other hand, was earlier reported to interact strongly with MAPK MPK6 in yeast two-hybrid assays, and the loss-of-function mkp1 mutant displayed mis-regulation of MPK6 activity specifically in response to genotoxic stress in planta (20,21). Despite these indications of a functional relationship between AtMKP1 and MPK6, the ability of AtMKP1 to catalyze dephosphorylation of activated MAPKs has not been demonstrated experimentally.…”
mentioning
confidence: 99%
“…In fact, both AtPTP1 and AtDsPTP1 dephosphorylate and deactivate a MAPK protein (AtMPK4) in vitro (32,33). A putative DsPTP gene, AtMKP1, is essential for UV resistance in Arabidopsis (34).…”
mentioning
confidence: 99%
“…This was shown by expression profiling of wild-type vs. mkp1 mutant lines and increased resistance to salinity of mkp1 mutant plants. 115 During water stress, transpirational loss of water is reduced as stomata close in response to ABA. Using specific inhibitors, PTKs and PTPs have been involved in the signaling pathway leading to stomatal closure.…”
Section: 88mentioning
confidence: 99%
“…118,119 The Arabidopsis mkp1 mutant which was shown to be resistant to elevated salinity, is also hypersensitive to UV radiation. 115,118 Defense, cytoskeleton organization and response to hormones. The DsPTK BAK1 is the positive regulator of the signaling pathways induced by the BRs but also of the transduction cascade induced by the bacterial pathogen flagellin.…”
Section: Acknowledgmentsmentioning
confidence: 99%